What kinds of diversity are super? Hidden diversities and mobilities on a Mediterranean island. (November 2016) - Jaffe, Alexandra
Abstract: In this article, ethnographic data from the island of Corsica are used to explore the concept of superdiversity. The first looks at a historical society hike, tracing "hidden" forms of diversity at the micro-level that counterbalance normative, traditional narratives of language, place and culture. The second examines a new cultural park on the island that is both organized around heterogenous themes and, in the philosophy of its founder, exhibits "tactics of superdiversity" that disrupt conventional narratives and models of authenticity and coherence. Highlights: Exploration of "micro-superdiversity" in two ethnographic data sets on Corsica. Analysis of "tactics" and "stances" of superdiversity. Fine-grained analysis of interactional and representational texts.